The Relationship Between Hardiness and Psychological Well Being in Non-Regional Students - Mariska, Afina Syfa; Astuti, Kamsih (Program Studi Psikologi Universitas Bosowa, 2024)
Non-regional students face various challenges such as adapting from scratch, learning a new culture, new habits, new friends, a new living environment, as well as educational and social problems. From previous research, it is known that psychological well-being is influenced by several factors, one of which is hardiness. This study aims to determine the relationship between hardiness and psychological well-being in non-regional students. This study proposes a hypothesis that there is a positive relationship between hardiness and psychological well-being in non-regional students. The subjects in this study were 221 non regional students with an age range of 18-25 years. The data collection method used in this study is using the Psychological Well-Being Scale and the Hardiness Scale. The data analysis technique used is using product moment correlation. Based on the results of data analysis, the correlation coefficient (rxy) = 0.674 with p < 0.001 (p < 0.001) shows that the hypothesis proposed in this study is accepted, namely there is a positive relationship between hardiness and psychological well-being in non-regional students. The coefficient of determination (R2) is 0.455 so it can be said that the contribution of hardiness is 45.5% to psychological well-being and the remaining 54.5% is influenced by other factors. The practical implication of this research is the importance of improving psychological well-being in non regional students so that this will have a positive impact on academic achievement and a more optimal personal life.